Non-imidazole-based histamine H3 receptor antagonists with anticonvulsant activity in different seizure models in male adult rats - Sadek B; Saad A; Latacz G; Kuder K; Olejarz A; Karcz T; Stark H; Kiec´-Kononowicz K (Dove Medical Press, 2016)
Bassem Sadek,1 Ali Saad,1 Gniewomir Latacz,2 Kamil Kuder,2 Agnieszka Olejarz,2 Tadeusz Karcz,2 Holger Stark,3 Katarzyna Kieć-Kononowicz2 1Department of Pharmacology and Therapeutics, College of Medicine and Health Sciences, United Arab Emirates University, Al Ain, United Arab Emirates; 2Department of Technology and Biotechnology of Drugs, Faculty of Pharmacy, Jagiellonian University Medical College, Kraków, Poland; 3Department of Pharmaceutical and Medicinal Chemistry, Institute of Pharmaceutical and Medicinal Chemistry, Heinrich Heine University, Düsseldorf, Germany Abstract: A series of twelve novel non-imidazole-based ligands (3–14) was developed and evaluated for its in vitro binding properties at the human histamine H3 receptor (hH3R). The novel ligands were investigated for their in vivo protective effects in different seizure models in male adult rats. Among the H3R ligands (3–14) tested, ligand 14 showed significant and dose-dependent reduction in the duration of tonic hind limb extension in maximal electroshock (MES)-induced seizure model subsequent to acute systemic administration (5, 10, and 20 mg/kg, intraperitoneally), whereas ligands 4, 6, and 7 without appreciable protection in MES model were most promising in pentylenetetrazole (PTZ) model. Moreover, the protective effect observed for ligand 14 in MES model was lower than that observed for the reference drug phenytoin and was entirely abrogated when rats were co-administered with the brain-penetrant H1R antagonist pyrilamine (PYR) but not the brain-penetrant H2R antagonist zolantidine (ZOL), demonstrating that histaminergic neurotransmission by activation of postsynaptically located H1Rs seems to be involved in the protective action. On the contrary, PYR and ZOL failed to abrogate the full protection provided by 4 in PTZ model and the moderate protective effect by 14 in strychnine (STR) model. Moreover, the experimental and in silico estimation of properties such as metabolism was performed for five selected test compounds. Also, lipophilicity using planar reversed-phase thin-layer chromatography method was included for better understanding of the molecular properties of the tested compounds. Additionally, the absorption, distribution, metabolism, and elimination and toxicity parameters were evaluated for the most promising compounds 2, 4, 6, 7, and 14 utilizing in vitro methods. These interesting results highlight the potential of H3R ligands as new antiepileptic drugs or as adjuvants to available epilepsy medications. Keywords: histamine H3 receptors, antagonists, anticonvulsant, R-(α)-methyl-histamine, pyrilamine, zolantidine